One nation, two teams : repositioning the Toronto Blue Jays among the threat of a new entrant - Dalal, Keegan; Declercq, Lindee; Piché, Megan C.; Hyatt, Craig G.; Naraine, Michael L., 1987- (London : Human Kinetics, Inc, 2021)
This fictional case deals with the Toronto Blue Jays' response to the Montreal Expos rejoining Major League Baseball (MLB). The Jays' president is informed midway through the season that Montreal will be receiving a team through expansion or relocation. The Expos returning to MLB poses many threats and opportunities for the Toronto Blue Jays. As a result, the Blue Jays must consider the issue of national identity, which their brand has been strategically positioned around. The Jays are transitioning from being Canada's only team to sharing the market with the Expos. Nevertheless, the Expos' return to MLB provides the Blue Jays with an opportunity to explore new marketing strategies. Students are tasked with repositioning the Blue Jays' marketing strategy in response to the Expos.The case highlights reoccurring themes such as national identity, retro marketing, and rivalry; the two latter concepts are relatively new sport marketing research areas. The intention is to familiarize students with these new marketing concepts and their role in marketing and consumer behavior. The case questions will guide the students through a typical marketing plan process, giving them opportunities to think critically and justify their decisions before developing a campaign and promotions.brand management, national identity, nostalgia, rivalry, sport marketing.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports teams -- Management -- Case studies; Branding (Marketing) -- Case studies